THE ISSUE OF THE RECOVERY OF THE COLLECTIONS OF THE VILNIUS MUSEUM OF ANTIQUITIES - KERŠYTĖ, NASTAZIJA (Knygotyra, 2011)
Since the beginning of the 20th century until now, there have been several key issues to indicate why the restitution from Russia to Lithuania of the Vilnius Museum of Antiquities (1855–1865) collections that were removed by Tsarist Russian authorities to the Moscow Rumyantsev museum in 1868, and perhaps also in 1914, with other valuable collections of the Vilnius Museum under the Vilnius Public Library (1867–1915), is irrecoverable, except for a small amount (286) of their total. The positions regarding the restitution of Lithuanian cultural property, including that of the Vilnius Museum of Antiquities, from Russia is not always active enough and properly justified. Lithuania has no precise registers of the values removed from the Vilnius Museum of Antiquities to the Rumyantsev museum and other museums of Russia. The data in the information published by Russians about the amount of the values removed from the Vilnius Museum of Antiquities are understated. Lithuania, referring to the Peace Treaty with Russia (1920), conducted negotiations for the recovery of the Lithuanian cultural property removed to Russia. The expert negotiator Paulius Galaunė made significant additions to the Vilnius museum collection inventory which was published in the Antiquities Department of the Rumyantsev Museum inventory catalog in 1906. The four, so far unpublished, registers of the values removed from the Vilnius Museum of Antiquities in 1868, sent to the Rumyantsev museum by Pompey Batiushkov, Curator of the Vilnius Educational District reveal the scale of the removal – more than 10 000 items. In the beginning of the third decade of the 20th century, negotiations between Lithuania and Russia on the return of values of the Vilnius Museum of Antiquities failed because of the unsuccessful Polish claim to receive them and of the desire of Russians to strengthen the global importance of the Rumyantsev museum by adding values from the Vilnius Museum of Antiquities. In 1928, Poland received from the St. Petersburg Hermitage one item from the Vilnius Museum of Antiquities – a marble sculptural composition depicting Jadwiga with Jagiello – which after three years was transferred from Warsaw to the Polish Friends of Science Society in Vilnius (1907–1939). The Society declared that they were successors of the traditions of the Vilnius Museum of Antiquities and the Temporary Archaeology Commission, although the remains of the Vilnius Museum of Antiquities collections were inherited by the Museum of Archaeology (1921–1939) at Stefan Batory University, but not by the Society. In Soviet times, the historical continuity of the Vilnius Museum of Antiquities collections inheritance became the main pretext for its return to Vilnius. In 1956, 1966 and 1968, 285 items were returned from Russia to the History and Ethnography Museum of the LSSR Academy of Science (1952–1963) and the Museum of History-Ethnography of the LSSR (1963–1990). These museums were proclaimed the successors of the Vilnius Museum of Antiqui ties. An important predestination of the return was the social-ideological cohesion of Soviet Lithuania and the USSR, heritage funds, as well as professional efforts of the scientist and museum curator Adolfas Tautavičius. After 1990, Lithuania and Russia, like a number of other countries of the world, have accepted international agreements and guidelines recommended by the ICOM (International Council of Museums) Code of Professional Ethics which states the belonging of the collections to the locations where they were formed. However, overdue of the rest of Vilnius Museum of Antiquities collections for Lithuania warns that there must be legal intergovernmental agreements between Russia and Lithuania on the return of cultural property to Lithuania. There is a lack of an appropriate juridical position. The agreement between Russia and the Republic of Lithuania (29 07 1991) does not specify the return of cultural property from Russia to Lithuania. The mutual Cooperation Agreement between the Ministries of Culture (06 07 2009) just appealed to the discovery of the cultural property illegally exported to the territory of another state. According to the Lithuanian government decrees, programs, heritage laws, resolutions that refer to the issues of return of the cultural property to Lithuania, concrete recoveries from Russia have yet not been achieved. The National Museum of Lithuania is interested to recover the collections of the Vilnius Museum of Antiquities from the Russian Federation. The Museum, which keeps about 1000 items from those collections, is the successor of the Vilnius Museum of Antiquities. These items are only the remains of the collection of the Vilnius Museum of Antiquities, which were left in Vilnius by the Tsarist Russian authorities, and include also 285 items returned from Soviet Russia.